Behavioral disorder in people with an intellectual disability and epilepsy: A report of the Intellectual Disability Task Force of the Neuropsychiatric Commission of ILAE. Issue 3 (15th September 2016) - Kerr, Mike; Linehan, Christine; Brandt, Christian; Kanemoto, Kousuke; Kawasaki, Jun; Sugai, Kenji; Tadokoro, Yukari; Villanueva, Vicente; Wilmshurst, Jo; Wilson, Sarah
Summary: The management and needs of people with intellectual disability (ID) and epilepsy are well evidenced; less so, the comorbidity of behavioral disorder in this population. "Behavioral disorder" is defined as behaviors that are difficult or disruptive, including stereotypes, difficult or disruptive behavior, aggressive behavior toward other people, behaviors that lead to injury to self or others, and destruction of property. These have an important link to emotional disturbance. This report, produced by the Intellectual Disability Task Force of the Neuropsychiatric Commission of the ILAE, aims to provide a brief review of some key areas of concern regarding behavioral disorder among this population and proposes a range of research and clinical practice recommendations generated by task force members. The areas covered in this report were identified by experts in the field as being of specific relevance to the broad epilepsy community when considering behavioral disorder in persons with epilepsy and ID; they are not intended to be exhaustive. The practice recommendations are based on the authors' review of the limited research in this field combined with their experience supporting this population. These points are not graded but can be seen as expert opinion guiding future research and clinical practice.